(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The article analyzes the stages of restoration and development of museum work in the Kashkadarya region during the 1950s–1980s. It highlights the postwar transformations in museum activities, the policy of centralization, and the processes of reorganization. The study reveals the scientific and educational functions of museums and their role in shaping public consciousness. The research is based on archival materials and official reports. The revival of the Kashkadarya museum marked a new stage in the cultural life of the region.